Outlines of the Strategic Plan UIN Syarif Hidayatullah Jakarta: Heading towards becoming a Research University by the Year 2007 - Azra, Azyumardi (Studia Islamika, 2003)
What is meant by the term Research University? Essentially, a Research university is a university based upon a research tradition. The implications are broad, being that the university must have the capabilities and facilities to support the strengthening of this research tradition. In realizing these aspirations, there is a need to identify how prepared the university is to begin developments in the areas of academic, financial and administrative, institutional, and student affairs. This is necessary to obtain an objective evaluation of the actual capacity of the institution in the above four areas.DOI: 10.15408/sdi.v10i2.635